Ibnu Sina’s Mental Health - Rizkiah, Fina; Nano warno; Adi Setiawan; Yulian Rama Pri Handiki; Adelia Febrianty (Jurnal Spiritual Healing, 2024)
ABSTRACT In this era, human life relies on progress in science and technology, which in turn creates problems that must be faced physically, psychologically, socially and economically. Which ultimately causes a person to experience mental health disorders such as stress and depression, paranoia, schizophrenia, anxiety, bipolar, dimensionality, autism. In this regard, there has been debate among western scholars, medical circles and psychiatrists, psychologists and various other schools in identifying the causes of mental disorders and this has given rise to debate among scientists. Some scientists say that the problem of mental disorders starts from biological, biophysical, psychosocial, genetic and social factors. The method used in this research is descriptive analysis with a qualitative type of research. The results of the researchers show that modern psychology and western philosophers no longer see the issue of mental disorders as a metaphysical discussion, they only look at it from a social perspective and do not explain problems regarding the soul in discussions about health. mentally. They focus on medical problems that are related to physical or sociological causes and do not see them as metaphysical entities. Ibn Sina explains metaphysics and the relationship between body and soul on a philosophical basis for mental health. Ibn Sina proposed a more integrative approach to mental health disorders.